The importance of critical life moments: An explorative study of successful women with autism spectrum disorder. (August 2017) - Webster, Amanda A; Garvis, Susanne
Ten women with autism spectrum disorder participated in oral interviews in order to share their experiences since their diagnosis and to discuss the factors that had enabled them to achieve success in different aspects of their life. Participants were encouraged to share their perspectives on their success and to discuss the challenges they encountered in their daily lives and how they overcame these. Interviews were analysed using a narrative-themed approach. Participants indicated that both internal and external factors enabled them to achieve success in different aspects of their lives. These included being an agent of change, a changed identity after diagnosis, experiencing the belief of others in their capability and seeing themselves as a mentor to others. Their experiences with overcoming obstacles in their lives enabled them to develop self-efficacy and to shape their own success.